Towards a Sociology in Peru University Education - Ríos Burga, Jaime Rodolfo (2018)
This work seeks to locate some of the new situations and problems, models and policies, from the educational sociological theoretical reflection present in the Peruvian university in the actual global transformation. An analysis and understanding in their specific contexts of propagation and discourses that lead us to verify that today we are witnessing the consolidation of a new socio-educational structural asymmetry in the country.